Evaluasi Kemampuan Lahan di Desa Punggur Kecil Kecamatan Sungai Kakap Kabupaten Kubu Raya - Rahmansyah, Fathur; Hazriani, Rini; Manurung, Rinto (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2025)
The evaluation of land capability in Punggur Kecil Village, Sungai Kakap Sub-district, Kubu Raya Regency, West Borneo aims to assess land potential and limitations to support effective and sustainable land use planning in the area. This study used a grid method covering physical and chemical characteristics, as well as environmental factors such as topography, climate, and current land use patterns. Data were collected through field surveys, soil sampling, and physical and chemical laboratory analysis to determine key parameters such as soil pH, salinity, permeability, and fiber content. The evaluation results show that most of the land in Punggur Kecil Village has high potential for agricultural activities, especially for annual crops and plantation crops. The findings of this study are expected to provide guidance for better land use planning, as well as recommendations for sustainable management in Punggur Kecil Village, in order to increase productivity and sustainability of natural resources in accordance with Kubu Raya Regency Regional Regulation Number 7 of 2016 concerning Spatial Planning of Kubu Raya Regency 2016-2036 in the area of Punggur Kecil Village, Sungai Kakap District, Kubu Raya Regency, West Borneo